2014
DOI: 10.2485/jhtb.23.461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Carotid Artery Calcification seen on Panoramic Radiographs

Abstract: Among patients who visited our hospital with a chief complaint of disorders involving the oromandibular region, with suspected carotid artery calcification based on panoramic radiography, and who underwent computed tomography for a detailed examination of these disorders, there were four patients in whom a definitive diagnosis of carotid artery calcification was made. We herein provide an overview of these cases, along with a brief review of the relevant literature. When imaging findings suggestive of carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Panoramic radiographic imaging enables a wide view of the jawbone and thus could be useful as a method to screen for certain lesions that can occur in the maxillofacial area without symptoms. For example, some studies have reported incidental findings such as carotid artery calcification and osteoporosis [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Panoramic radiographic imaging enables a wide view of the jawbone and thus could be useful as a method to screen for certain lesions that can occur in the maxillofacial area without symptoms. For example, some studies have reported incidental findings such as carotid artery calcification and osteoporosis [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%